Climatologia das ondas de frio e de calor para o Rio Grande do Sul e sua relação com El Niño e La Niña - Firpo, Mári Ândrea Feldman (2008)
In this paper the results of Cold and heat waves and their relationships with to El Niño and La Niña events in 13 meteorological stations in Rio Grande do Sul along the years of 1967 up to 2005 are presented. Daily frost and maximum and minimum air temperature data were used. The anomalies were obtained subtracting the average year (climatological normal to the data set) of each year which was analyzed. Cold waves were considered the period of five or more days of consecutive negative minimum temperature and hot waves for the same time but in positive anomalies and maximum temperature. It was also used a quantil technique to split in quartile segments the highest anomalies values and the anomalies interval values of each wave in order to classify them according to its intensity and termic amplitude respectively. Only the waves of five days were classified. Analyzing the waves average behavior it was observed that the cold ones happen more in the winter and that there is an homogeneity related to its distribution in the state. On the other hand, the heat waves happen also in the colder months, but their distribution is heterogeneous, happening more in the meteorological stations located more in the northern part of the state. The relationships between frosts and waves it was noticed that there is a positive correlation between the frosts average number and the cold waves and negatives average number to the heat ones, statistically significant at 1% level in the months of June and July, but not in August. The relationships between cold and heat waves and the ENSO events show that, in general, the occurrence of La Niña increases the number of cold waves and decreases the heat waves in Rio Grande do Sul, while the El Niño increases the heat waves and decreases the cold waves. It was also analyzed the frost relationships with ENSO events and it was noted that in the months of June and July there is a higher occurrence of frosts during La Niñas. However, in August this occurrence is higher during El Niños